Assessment of DNA damage of smooth muscle cells in tunica media of human arterial allografts using Comet assay method - Miroslava Jandová; Alexander Pilin; Ivan Mazura; Radka Lainková; Ivan Matia; Myroslav Salmay; Pavel Měřička; Ondřej Pecha; Libor Janoušek; Tomáš Grus; Rudolf Špunda; Jaroslav Lindner; et al. (PLoS ONE, 2025)
During the harvest and subsequent processing of blood vessels for allogeneic transplantation, DNA damage can occur. A suitable method for quantifying this damage may be the comet assay, also known as the single cell gel electrophoresis assay, which is used to measure DNA damage at the single-cell level. We evaluated the key indicators of muscle cell DNA damage in the tunica media of arteries by using the comet assay with four groups: (1) cryopreserved grafts thawed slowly, (2) cryopreserved grafts thawed rapidly, (3) cold-preserved “fresh” grafts harvested as part of a multiorgan procurement, and (4) cadaveric arterial graft harvested at autopsy. Kruskal-Wallis multiple-comparison testing identified a statistically significant difference between rapidly thawed grafts and multiorgan harvested fresh grafts. Evans’ correlation criterion indicated a moderately strong correlation between the percentage of DNA in the comet head and warm ischemia duration in the group of slowly thawed grafts, and between the percentage of DNA in the comet head and cold ischemia duration in the group of cadaveric grafts. No association of come assay parameters with age was demonstrated. Comet assay showed that the cryopreservation and storage processes described in this study did not lower the DNA content in comparison with fresh grafts collected during multiorgan harvests in operating rooms and that DNA content was not influenced by the type of thawing protocol.